Biomonitoring of the genotoxic potentials of two edible insects species in vitro - Turkez, Hasan; Incekara, Umit; Erman, Orhan (Entomological Soc Turkey, Ege Univ, 2010)
In this study, we evaluated the genotoxic potentials of water soluble extracts of grasshoppers, Saga ephippigera ephippigera Fischer de Waldheim, 1846 and Callimenus dilatatus (Stal, 1876) (Orthoptera) on cultured human blood cells. The chromosome aberration (CA) and micronucleus (MN) tests were used to assess the DNA and chromosomal damage produced by aqueous extracts in vitro. The extracts were added to the cultures at eight different concentrations (1, 5, 10, 20, 25, 50, 75 and 100 mg/l). Our results indicated that these extracts did not show genotoxic effects at the tested concentrations. We conclude that this in vitro approach for biomonitoring genotoxicity assessment may be useful to compare the potential health risks of edible insects.
Keywords: Edible insects; genotoxicity; human blood culture; micronucleus; chromosome aberration